Re-imaging the Moral Order of Urban Space: Religion and Photography in Winnipeg, 1900-1914 - Opp, James (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2002)
AbstractThe arrival of the Reverend J.S. Woodsworth as the Superintendent of Winnipeg's All Peoples' Mission in 1907 coincided with a strategic shift in the visual representation of urban space in many Canadian Methodist publications. Traditional photographs of churches and ministers were soon accompanied by images of crowded tenements, impoverished conditions, and unsupervised children on the street. This paper examines the introduction of a social documentary style of photography and analyses how these images functioned within the context of the emerging social gospel and widespread middle-class anxieties over the “problem” of the city. This visual technology appealed to the new social reform emphasis on “surveying” conditions, but photography's inherent claim to represent an objective reality was overlaid with gendered moral boundaries, particularly in the space that surrounded the bodies of children. The re-imaging of urban space was part of a broader narrative that positioned the religious response to the city as both a moral and an environmental problem.